Hearing Aid Use and Mild Hearing Impairment: Learnings from Big Data - Timmer, Barbra H. B.; Hickson, Louise; Launer, Stefan (Journal of the American Academy of Audiology, 2017)
Previous research, mostly reliant on self-reports, has indicated that hearing aid (HA) use is related to the degree of hearing impairment (HI). No large-scale investigation of the relationship between data-logged HA use and HI has been conducted to date.This study aimed to investigate if objective measures of overall daily HA use and HA use in various listening environments are different for adults with mild HI compared to adults with moderate HI.This retrospective study used data extracted from a database of fitting appointments from an international group of HA providers. Only data from the participants’ most recent fitting appointment were included in the final dataset.A total of 8,489 bilateral HA fittings of adults over the age of 18 yr, conducted between January 2013 and June 2014, were included. Participants were subsequently allocated to HI groups, based on British Society of Audiology and American Speech-Language-Hearing Association audiometric descriptors.Fitting data from participating HA providers were regularly transferred to a central server. The data, with all personal information except age and gender removed, contained participants’ four-frequency average (at 500, 1000, 2000, and 4000 Hz) as well as information on HA characteristics and usage. Following data cleaning, bivariate and post hoc statistical analyses were conducted.The total sample of adults’ average daily HA use was 8.52 hr (interquartile range [IQR] = 5.49–11.77) in the left ear and 8.51 hr (IQR = 5.49–11.72) in the right ear. With a few exceptions, there were no statistical differences between hours of HA use for participants with mild HI compared to those with moderate impairment. Across all mild and moderate HI groups, the most common overall HA usage was between 8 and 12 hr per day. Other factors such as age, gender, and HA style also showed no relationship to hours of use. HAs were used, on average, for 7 hr (IQR = 4.27–9.96) per day in quiet and 1 hr (IQR = 0.33–1.41) per day in noisy listening situations.Clinical populations with mild HI use HAs as frequently as those with a moderate HI. These findings support the recommendation of HAs for adults with milder degrees of HI.
Keywords: hearing aids; hearing impairment